Networked Learning as a Framing of Society - Brandén, Henrik (Proceedings of the International Conference on Networked Learning, 2024)
The main purpose of this paper is to explore the idea of conceptualising networked learning, not as a kind of human activity, but as a way of viewing human activities. The hope is to promote collaborations and connections between the field of networked learning and other fields, in ways that may ultimately transform, mutate, and hybridise the fields. To achieve this, four metaphors of society is outlined. These are named the biosphere, the distorted reality, the community, and the market. The metaphors serve as foundations for four different framings of society that directs attention and raises questions about learning. It is noted that by combining several frames, it may be possible to approach networked learning in a more thoughtful, nuanced, and well-balanced way. It is also noted that the use of frames could make it possible to move beyond what has been called the impasse of ideology in the field of networked learning.